Growth of marine biofilms and macrofouling organisms on biocide-infused, 3D-printed thermoplastics - Shimeta, Jeff; Wilding-McBride, Gemma; Bott, Nathan J.; Piola, Richard; Santander, Rene; Leary, Martin; Scardino, Andrew J. (Frontiers in Marine Science, 2023)
3D printing has become widely used to rapidly prototype and manufacture novel or bespoke objects or replacement components in a wide range of marine industries, engineering, and research. 3D-printed objects are subject to marine biofouling, impacting their operation and longevity. Application of antifouling paints or coatings adds costly and time-consuming steps and may interfere with the function of fine surface features, counteracting some of the benefits of 3D-printing technology. We measured the antifouling performance of two 3D-printing thermoplastics embedded with antifouling biocides to create 3D-printed materials with inherent antifouling properties: 1) polycaprolactone (PCL) mixed with the organic biocide dichlorooctylisothiazolinone (DCOIT) and extruded as 3D-printing filament, and 2) a commercial polylactic acid (PLA) 3D-printing filament with embedded copper powder. Settlement plates printed from these thermoplastics (“PCL-DCOIT” and “PLA-Cu”, respectively) and deployed in temperate, coastal marine water for 17 weeks during summer remained free of macrofouling. A biofilm developed, and 16S and 18S rRNA metabarcoding analyses revealed that early stage biofilms (at 5 and 12 weeks) had dramatically altered assemblage structures of both prokaryotes and eukaryotes compared to natural biofilms. The assemblage on PCL-DCOIT had reduced microbial diversity, strong dominance of Proteobacteria and chlorophytes, and almost complete absence of Flavobacteriia, Cyanobacteria, and diatoms. In contrast, the biofilm on PLA-Cu had a dominance of Flavobacteriia over Proteobacteria, and resistance to chlorophytes, yet similar to PCL-DCOIT it resisted Cyanobacteria and diatoms. Such alterations to biofilm microbial assemblages could influence microbial dynamics, biofilm growth, and settlement cues to which biofouler propagules respond. At 17 weeks, the two biocide-embedded thermoplastics completely resisted macrofouling, equally well as three commercial antifouling coatings (Intercept 8500, Hempaguard X7, Hempasil X3); however, PCL-DCOIT was more extensively covered by a microalgal film (79%, evidently chlorophytes) than were the commercial coatings, and PLA-Cu had the most settled detritus (100% cover). Biofilm assemblages on the commercial coatings were investigated for comparison, with PCL-DCOIT standing out due to its almost complete resistance to Flavobacteriia. Thermoplastic 3D-printing filaments with embedded biocides show promise for producing 3D-printed objects with inherent antifouling properties, avoiding or lessening the need to apply antifouling coatings, and possibly extending their service lifetime.